THE USE OF CONTEMPORARY DANCING VIDEO FOR NARRATIVE WRITING - Utama, Febry Putra; Sutapa Y, Y Gatot; Riyanti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aimed of this reseach was to find out the effectiveness of Contemporary Dancing Video in teaching students writing narrative to year-10 students of MA Negeri 2 Pontianak in academic year 2017/2018. The population of this research was all year-10 students of MA Negeri 2 Pontianak in academic year 2017/2018 and the researcher took the sample by using cluster random sampling to determined the participant of the research which consisted of 39 students. From the data of the finding, itrevealed that the technique could make the students narrative writing ability increased significantly. It can be seen when the students tried to share and exchange their opinion and presented the discussion result in front of the class. The students put the core of narrative plot when presenting the story of the video.The research result showed that the technique was effective to enhance students narrative writing text due to the increasing for students’ achievements in narrative writing. It proved by the t-test calculation result which was higher than t-critical value (7.96 > 1.68). The effect size was 1.25 and categorized as high. As the conclusion, the media was able to be used in enhancing students’ ability in writing narrative text and the effect was positive. The researcher recommends this media as a variation in teaching process, especially in teaching writing narrative text. Keywords: Contemporary dancing video, Narrative text, teaching writing.